APAKAH MEDIA JEMURAN ANGKA DENGAN TALKING STICK DAPAT MENINGKATKAN HASIL BELAJAR MATEMATIKA? - Pramita, Monika Amilia Lindi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low mathematics learning outcomes are caused by the lack of variation in the learning media used. The purpose of this study was to explore the effect of number drying media with talking sticks on mathematics learning outcomes. The study used a quantitative method in the form of Pre-Experimental Design with a One Group Pretest-Posttest Design research design. The population consisted of 55 second-grade students of SDN 29 Nenak Tembulan with a sample of 28 students. The data collection technique was a measurement technique, with a data collection tool in the form of test questions. The data were analyzed and the results obtained showed a significant effect, namely increasing student learning outcomes by 30.17%.